Perilaku Sosial Remaja di Era Media Sosial: Analisis dalam Perspektif Psikologi Pendidikan Islam - Ahmad Ainun Najib; Moh. Arvani Zakky Al Kamil; Siti Lia Munawaroh (Jurnal Muria Research Guidance and Counseling (MRGC), 2026)
The digital era and the dominance of social media have significantly transformed adolescents’ patterns of interaction and social behavior. This study employs a Systematic Literature Review (SLR) method based on PRISMA guidelines and follows Snyder’s recommendations to ensure a systematic and comprehensive analysis. Data were collected from Google Scholar, SINTA, and Scopus using keywords related to adolescent social behavior, social media, and Islamic educational psychology. Content analysis was applied to identify key themes. The findings indicate that social media has a dual impact: it enhances access to information, religious motivation, and spiritual understanding, but also leads to addiction, declining communication ethics, and exposure to negative content. The intensity of social media use also alters adolescents’ social structures. From the perspective of Islamic educational psychology, digital literacy and the strengthening of Islamic character education are essential. This study highlights the crucial role of Islamic education and identifies research gaps as a basis for future studies.